1996
DOI: 10.1007/bf00023892
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seedling selection for salinity tolerance in potato (Solanum tuberosum L.)

Abstract: Salt-tolerance in potato (Solanum tuberosum L .) was selected on the basis of germination and survival of seed sown in trays of perlite suspended in either 75 or 150 mM NaCl . Salinity reduced the germination of seed . Genetic differences in salt-tolerance were apparent with salt reducing germination more in seed collected from cv . Cara than in that collected from cv. Maris Piper. Progeny from the seedling selection were then grown to maturity to produce tubers .The relative tolerance of the parental cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…This indicates that Kennebec is a relatively salt‐tolerant cultivar compared with Concord, which is very sensitive to salt. This is in agreement with the findings of Jefferies (1996), who proposed that genetic variations in salt tolerance exist in potato cultivars. The reduction in growth parameters under salt stress in both potato cultivars in our experiments confirmed previous studies that potato was a relatively salt‐sensitive crop (Backhosen et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that Kennebec is a relatively salt‐tolerant cultivar compared with Concord, which is very sensitive to salt. This is in agreement with the findings of Jefferies (1996), who proposed that genetic variations in salt tolerance exist in potato cultivars. The reduction in growth parameters under salt stress in both potato cultivars in our experiments confirmed previous studies that potato was a relatively salt‐sensitive crop (Backhosen et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Levy (1992) and Jefferies (1996) reported that salinity retarded the germination of seed tuber or true potato seeds. In this experiment, the plants failed to achieve full emergence at higher salt levels due to the rot of the seed tubers in the saline soil over a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the capacity for salt tolerance in transgenic plants is often affected by the inserted position on the host genomes, the copy number of the insertions, and the methylation status of the AtNHX1 gene (Tian et al, 2011). A number of methods involving different morphological and physiological parameters have been used to evaluate the salt tolerance of plants ( Jefferies, 1996;Shaterian et al, 2008), but a standardized method for the evaluation of salt tolerance has not been established due to limited knowledge of the genetic and physiological mechanisms responsible for salt tolerance in different plant species. Many growth traits and the associated physiological parameters to salt pathways have been considered to be critical for salt tolerance ( Jefferies, 1996;Katerji et al, 2003;Shaterian et al, 2008;Tian et al, 2011), yet any single growth trait has not been proven to be powerful enough in differentiating the salt tolerance of different plants (Mansour et al, 2005;Hu et al, 2007;Munns and Tester, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic evaluation of the salt tolerance of such transgenic potato is lacking. Furthermore, survival rate has been used in the evaluation of salt tolerance in potato breeding ( Jefferies, 1996), and total chlorophyll and proline contents and Na + in leaves are considered as the indicators of enhanced salt tolerance in transgenic plants (Tian et al, 2011;Donia et al, 2012). Furthermore, survival rate has been used in the evaluation of salt tolerance in potato breeding ( Jefferies, 1996), and total chlorophyll and proline contents and Na + in leaves are considered as the indicators of enhanced salt tolerance in transgenic plants (Tian et al, 2011;Donia et al, 2012).…”
Section: Assessment Of Salt Tolerance In Transgenicmentioning
confidence: 99%
See 1 more Smart Citation